WRITING LEARNING STRATEGY AND READING POETRY BASED FOR TRADITIONAL GAMES CRITICAL THINKING PROCESS - Masayu Gay (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
Critical thinking is the thinking ability that must be possessed by students through learning to write and read poetry. The indicators of critical thinking ability in writing and reading traditional game-based poetry are (1) knowing the problem, (2) collecting and compiling information, (3) organizing, (4) analyzing, (5) reconstructing, (6) informing, 7) apply or inform. The process of critical thinking in learning to write and read poetry based on traditional games (egrang) can develop critical thinking skills of elementary school students, with learning styles, first, teachers review the curriculum and formulate basic competencies and competency standards. Second, teachers and students make observations. Third, Teacher ensures that students have experience playing stilts. Fourth, students practice traditional game play. Fifth, teachers and students are elaborating. Sixth, students collaborate to record the materials used as a game. Seventh, the stage of writing and reading poetry. Eighth, the stage of communicating. Ninth, stage of reflection. This learning model can train students' thinking power, provide ease of writing and reading, fostering cooperation and social sensitivity. The quality of playing stilts, discipline, courage, patience, focus / concentration, and confidence.